Kombinasi Balanced Scorecard dan Objective Matrix Untuk Penilaian Kinerja Perguruan Tinggi - Mahmudi, A Aviv; Surarso, Bayu; Subagio, Agus (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
Working Assessment is very essential aspect for a college to keep its excellent quality to face tight competition in either national or international level. The working assessment can be implemented to compare the result with organization strategy, and can also help to plan the upcoming strategy to achieve the final target of organization. The combination of Balanced Scorecard and OMAX is aimed at building the information system of working assessment in a college. Balanced Scorecard in the college is used to determine the strategic purposes, KPI and target, optimistic and pessimistic value. The scoring of each KPI uses AHP method; the scoring of KPI influences on general working score. The scoring of working assessment uses Objective Matrix (OMAX) method to know the total result indicator stated by the college, and can find out the total result indicator of each working criterion. The combination of BSC and OMAX can avoid the use of overwhelming data because this model focused on four perspectives, with the important key indicator of a college. Besides, the four perspectives can avoid the orientation of short-term target, because OMAX developed the more obvious frame of time that also focused on the long-term target. This combination was a good integration that can afford to modify hybrid model in determining the score card of a college. BSC changed into the form of OMAX that presented a target in the long period. This combination is also a good integration that can afford to modify a hybrid model in determining the scorecard of the college. BSC changes into the form of OMAX that presents the long-term target. Â  Keywords: AHP; Balanced scorecard; OMAX; Work assessment; College